Cell fusion dynamics: mechanisms of multinucleation in osteoclasts and macrophages - Hideaki Sabe; Yasuhito Yahara; Masaru Ishii (BMC, 2024)
Abstract Cell-cell fusion is a vital biological process where the membranes of two or more cells merge to form a syncytium. This phenomenon is critical in various physiological and pathological contexts, including embryonic development, tissue repair, immune responses, and the progression of several diseases. Osteoclasts, which are cells from the monocyte/macrophage lineage responsible for bone resorption, have enhanced functionality due to cell fusion. Additionally, other multinucleated giant cells (MGCs) also arise from the fusion of monocytes and macrophages, typically during chronic inflammation and reactions to foreign materials such as prostheses or medical devices. Foreign body giant cells (FBGCs) and Langhans giant cells (LGCs) emerge only under pathological conditions and are involved in phagocytosis, antigen presentation, and the secretion of inflammatory mediators. This review provides a comprehensive overview of the mechanisms underlying the formation of multinucleated cells, with a particular emphasis on macrophages and osteoclasts. Elucidating the intracellular structures, signaling cascades, and fusion-mediating proteins involved in cell-cell fusion enhances our understanding of this fundamental biological process and helps identify potential therapeutic targets for disorders mediated by cell fusion.